Tempos e espaços de produção de saberes de alunos da educação de jovens e adultos (EJA) - Prigol, Cassilda Salete (Universidade do Vale do Rio do Sinos, 2006)
This dissertation is the result of a master’s degree research accomplished in a Post-graduation Program in Education at Vale do Rio dos Sinos University (UNISINOS). The research places in the field of studies work and education and presents as reflection purpose the production of students’ acquirements of Education for Youth and Adults (EJA-Educação de Jovens e Adultos). To develop this work it was decided by a qualitative research, priorizing the investigation of time and space of students’ acquirements in a private school in Erechim-RS. It was searched a theory foundation in authors like Paulo Freire, Bernard Charlot, Fernando Savater, Miguel Arroyo et al, who will be quoted along this work. Thus, it is emphasized that the spaces of knowledge production are beyond the school institution and need to be considered mainly in Education of adults. Considering life experience, acquired knowledge in social environment and work place of each student, gives to the school systematic learning a new dimension and a new
Keywords: produção de conhecimento; saberes do trabalho; jovens e adultos; work acquirements; knowledge production; youth and adults; Ciências Humanas